Eculizumab reverses the potentially fatal effects of kidney graft reperfusion injury. (16th December 2013) - Kaabak, Michael; Babenko, Nadezhda; Kuznetsov, Oleg; Matveev, Alexander; Minina, Marina; Platova, Elena; Morozova, Margaret; Novozhilova, Tatyana
Abstract Half an hour after reperfusion, the kidney, transplanted to the infant from an adult brain dead standard criteria donor, became flabby and acquired blue color. Hyperacute rejection was suspected as a consequence of false negative cross match, and eculizumab was administered with the purpose to treat antibody‐mediated injury, with fast and clear effect. The patient's blood was tested for donor‐specific antibodies on the next day, and results were negative. We attribute graft damage to reperfusion injury and explain eculizumab's effectiveness to its ability to prevent progression of reperfusion injury.